Penerapan Desain Produk dalam Bentuk Packaging Produk Hasil Cetak 3D di Sekolah SMA Al Kamal Jakarta Barat - Mesah Nur Sejati; Pillar Anugrah Hadi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Based on the academic background of SMA AL KAMAL West Jakarta, we can identify existing issues that we must address within our discipline, particularly in screen printing techniques. This is driven by our community service program, which focuses on creative and innovative skills in screen printing pouch products. Furthermore, our Student Creativity Program (PKM) program at SMA AL KAMAL West Jakarta aims to strengthen the school's partnership with Mercu Buana University, which specializes in product design. The program, focused on screen printing pouch products, aims to benefit SMA AL KAMAL West Jakarta, enabling students to develop skills in screen printing techniques and produce functional pouch merchandise.